(untitled) (Journal Of Educational and Psychological Researches, 2011)
This research has targeted a prototype for the continuous development correction of the educational programs based on analyzing (61) evaluation studies through the correction study standard that prepared by the researcher, then she found indicators that approved by applying (Delphy) method. The research aim has achieved through preparing a prototype which consists of four stages; they are: 1. Correcting the educational program framework 2. Correcting the educational program plan 3. Correcting the implementing processes of the educational program 4. Correcting the educational program outputs. It has been developed some recommendations and proposals.